Self-Withdrawal as Individual Liberty in Response to Gender Inequality in Circe by Madeline Miller - Nada Kamila Chairunisa; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2025)
Women are frequently controlled and subjugated as a result of gender inequality, which drives them to seek independence. In Madeline Miller’s novel Circe, the protagonist’s act of self-withdrawal represents an assertion of individual liberty in response to patriarchal oppression. This study examines how gender inequality shapes Circe’s decision to isolate herself and how her withdrawal becomes a form of resistance and self-empowerment, analyzed through the lens of liberal feminism as outlined by Rosemarie Tong. This research employs a qualitative descriptive method, using the novel Circe as the primary data source. The findings reveal that Circe experiences various forms of gender inequality, which drive her to withdraw and develop her own identity and abilities. Ultimately, this self-withdrawal enables her to achieve a sense of individual liberty and personal agency. In conclusion, the novel depicts self-withdrawal as a deliberate and empowering response to gender inequality, consistent with the components of liberal feminism.